RESEARCH AND ASSESSMENT OF FIRE RISKS IN HOTEL AND RESTAURANT ESTABLISHMENTS IN UKRAINE - POGREBNYAK, Andriy; VISHNIKINA, Olena; KUCHER, Marharyta; SABIROV, Oleksandr; GRYTSENKO, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article analyzes the state of fire safety in the hotel and restaurant business establishments of Ukraine from 2016 to 2021, assesses the causes and consequences of fire incidents, and provides recommendations for preventing fire hazards and minimizing negative impacts. The purpose of the article is defined as conducting an analysis and providing an assessment of the entirety of existing fire risks, their causes, consequences, and recommendations for their prevention or minimization. To achieve this goal, tasks were carried out to systematize and process statistical data obtained from open sources regarding the number of recorded fire incidents in hotel and restaurant establishments during the specified period. The primary causes of fires were analyzed, along with the set of factors that form these causes. The main fire safety issues typical for most hotels and restaurants in the country were highlighted. Additionally, the possible consequences of fire hazards were systematized and analyzed. The final task of the article is to provide recommendations for the elimination, minimization, or optimization of fire risks. Among the key problems in the field of fire safety in hospitality and restaurant establishments, the following can be identified: insufficient training of owners and staff in fire safety regulations, insufficient awareness of the necessity and importance of adhering to fire safety rules, lack of regular fire evacuation drills, outdated fire-fighting equipment and fire alarm systems (in some establishments, the wear rate reached 90%), lack of special equipment (smoke and temperature detectors, fire alarms, fire suppression systems) or non-compliance with the rules for their operation, and inadequate organization and coordination between fire safety services and the management of establishments. Understanding fire risks in the hospitality and restaurant sector requires a comprehensive analysis of the structural features of establishments that can affect the level of fire safety. This analysis includes the evaluation of building structures, ventilation systems, fire protection measures, and evacuation routes. A retrospective analysis of the causes and consequences of fires allows for identifying a consistent trend both in the ranking of causes and in the available consequences. The conducted fire risk assessment in hotel and restaurant establishments allows for providing necessary recommendations for implementation. The required measures include the introduction of a staff training system on fire safety issues, the inspection and modernization of the fire safety infrastructure of hotels and restaurants, and the strengthening of oversight by government authorities regarding compliance with Ukrainian legislation. It is also important to enhance educational and training programs for personnel on fire safety to ensure a high level of readiness for emergencies and prevent potential tragedies and damages. Furthermore, continuous personnel training on fire safety regulations, fire prevention, and incident management in hospitality and restaurant establishments, as well as basic first aid procedures, is essential. Another recommendation, equally important, is the need to attract additional investments to implement modern methods and measures for complying with fire safety legislation. While safety policies involve additional costs (sometimes quite significant), long-standing international and domestic experience with investing in business security systems demonstrates significant strategic advantages of such an approach.